Field epidemiology training programmes in the Asia-Pacific: what is best practice for supervision? - Forbes, Owen; Davis, Stephanie; Dyda, Amalie; Rosewell, Alexander; Williams, Stephanie; Kirk, Martyn; Roces, Maria Concepcion; Lim-Quizon, Maria Consorcia; Viney, Kerri (Western Pacific Surveillance and Response, 2019)
Introduction: Field epidemiology training programmes (FETPs) emphasize competency-based training and learning by doing. Supervision of FETP trainees is critical for programmes to achieve learning outcomes. We sought to address a knowledge gap regarding what constitutes effective FETP supervision.Methods: We investigated FETP supervision using a mixed-methods approach. Quantitative data were collected through a survey of FETP directors. Qualitative data included written feedback from the survey and a focus group discussion (FGD) conducted with FETP supervisors at the 8th South-East Asia and Western Pacific Bi-regional TEPHINET Conference. FGD questions focused on effective supervisory qualities and activities and challenges to effective supervision. We calculated descriptive statistics for quantitative data and analysed qualitative data using a deductive content analysis approach.Results: Eleven FETP directors responded to the survey and 23 participated in the FGD. Overall, supervision was seen as very important for trainee outcomes. Participants identified the different roles of academic and field supervisors but emphasized the importance of an enabling and supporting attitude towards trainees. Soft skills and interpersonal abilities were among the most important qualities identified for effective supervision. Key challenges identified included a lack of consistency in supervisors’ technical knowledge and the difficulty of finding candidate supervisors with sufficient interest, availability and motivation for supervision.Discussion: Several practical recommendations arose from this study for supervision in FETPs, including recruiting and training supervisors with a more holistic range of skills. Our findings also provide key points for current FETP supervisors to consider to improve their own practice.